2019
DOI: 10.1590/1678-4162-10412
|View full text |Cite
|
Sign up to set email alerts
|

Additive effect of pulp pequi oil (Caryocar brasiliense Camb.) on the biocompatibility of collagen and gelatin membranes in subcutaneous implants

Abstract: Trauma or disease inflicted by tissue injuries may cause tissue degeneration. The use of biomaterials for direct or indirect repair has emerged as a promising alternative, and has become an important research topic. The pequi fruit (Caryocar brasiliense Camb.) has shown antifungal, antibacterial, anti-inflammatory, healing, antitumor, and antioxidant properties. The objective of this study was to develop a new biomaterial using a combination of collagen, gelatin, and pulp pequi oil, and to evaluate its biocomp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Pequi almonds contain approximately 50% oil, which may be utilized to produce food, cosmetics, chemicals, and biofuels [ 1 , 2 , 7 , 8 ]. Rabbers et al [ 9 ] reported that pequi oil is high in unsaturated fatty acids and possesses anti-inflammatory, antibacterial, antifungal, curative, antioxidant, and antitumor properties [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pequi almonds contain approximately 50% oil, which may be utilized to produce food, cosmetics, chemicals, and biofuels [ 1 , 2 , 7 , 8 ]. Rabbers et al [ 9 ] reported that pequi oil is high in unsaturated fatty acids and possesses anti-inflammatory, antibacterial, antifungal, curative, antioxidant, and antitumor properties [ 10 ].…”
Section: Introductionmentioning
confidence: 99%